MANAGING DUAL PATHOLOGIES: NEPHRECTOMY FOR RENAL CELL CARCINOMA IN A PATIENT WITH SEVERE TRICUSPID VALVE REGURGITATION - Stanoevska, Milica; Gavrilovska-Brzanov Aleksandra; Panovska Petrusheva, Aleksandra; Temelkovska Stevanovska, Marina; Chavkoska, Marina (Department of Anaesthesia and Reanimation, Faculty of Medicine, Ss. Cyril and Methodius University in Skopje, R.N. Macedonia, 2025)
Renal cell carcinoma (RCC) is the most prevalent form of kidney cancer.Tricuspid regurgitation is a condition marked by the reverse flow of blood from the right ventricle into the right atrium and necessitates thorough assessment to ascertain its severity and effect on heart function. In this case, we present a 57-years-old male patient with symptomatic renal cell carcinoma and a severe tricuspid valve regurgitation. The performed open nephrectomy went uneventfully. While the patient was successfully and safely managed from an anesthesiology standpoint despite his comorbidities, performing the procedure in a resource-limited setting posed significant challenges. In such environments, the lack of immediate access to advanced hemodynamic monitoring, cardiothoracic surgical support and perioperative cardiac interventions increases the complexity of managing patients with dual pathologies. Ideally, conducting nephrectomy in an operating theater equipped for simultaneous surgical interventions, addressing both the renal pathology and potential worsening of tricuspid valve regurgitation, with a cardiothoracic team on standby, would have provided a safer approach. However, in settings with constrained resources, optimizing intraoperative management, ensuring rigorous hemodynamic monitoring, and coordinating multidisciplinary teams within the available infrastructure become critical for achieving favorable outcomes.
Keywords: renal cell carcinoma; simultaneous surgery; tricuspid valve regurgitation